Understanding the Role of the Ottawa Ankle Rules in Physicians' Radiography Decisions: A Social Judgment Analysis Approach - Syrowatka, Ania (Université d'Ottawa / University of Ottawa, 2012)
Clinical decision rules improve health care fidelity, benefit patients, physicians and healthcare systems, without reducing patient safety or satisfaction, while promoting cost-effective practice standards. It is critical to appropriately and consistently apply clinical decision rules to realize these benefits. The objective of this thesis was to understand how physicians use the Ottawa Ankle Rules to guide radiography decision-making. The study employed a clinical judgment survey targeting members of the Canadian Association of Emergency Physicians. Statistical analyses were informed by the Brunswik Lens Model and Social Judgment Analysis. Physicians’ overall agreement with the ankle rule was high, but can be improved. Physicians placed greatest value on rule-based cues, while considering non-rule-based cues as moderately important. There is room to improve physician agreement with the ankle rule and use of rule-based cues through knowledge translation interventions. Further development of this Lens Modeling technique could lend itself to a valuable cognitive behavioral intervention.
Keywords: Evidence-Based Medicine; Knowledge Translation; Clinical Decision Rules; Ottawa Ankle Rules; Social Judgment Analysis; Brunswik Lens Model; Clinical Judgment Survey